Grandmothers and the gender gap in the Mexican labor market - Miguel Ángel Talamas Marcos (Inter-American Development Bank (IDB), 2022)
This paper estimates the effect of childcare availability on parents' employment probability using the timing of death of grandmothers-the primary childcare providers in Mexico-as identifying variation. I use a triple-difference to disentangle the effect of coinhabiting grandmothers' deaths due to their impact on childcare from their effects due to alternative mechanisms. Through their impact on childcare availability, grandmothers' deaths reduce mothers' employment rate by 12 percentage points (27 percent) and do not affect fathers' employment rate. The negative effect on mothers' employment is smaller where public daycare is more available, or private daycare or schools are more affordable.
Keywords: D10; J22; J16; J24; 330; Gender gap; Triple-difference; Motherhood penalty; Childcare; Mexico